(3bjGS GdYdGbGJ GdEbJUGOjIs - (3eMeO dWaj(B, (3aQMGJs ((3HfZGRj(B:s (3OGQ GdLeGgjQjI ddfTQ hGdJhRjY(B,s, 1986)
(3GdYdGbI Hjf eJZjQjf(B- (3JMdjd GdEfMOGQ GdHSjW(B- (3hUa GdYdGbGJ GdSdhcjI hcjajI bjGSgG(B- (3GSJYeGdGJ GdfehPL GdebOQ(B- (3HYV eTGcd JMdjd GdEfMOGQ(B- (3JMdjd GdEfMOGQ GdYGe(B- (3HYV GdYdGbGJ GdEbJUGOjI(B- (3eTGcd fehPL GdEfMOGQ GdYGe(B- (3acQI YGeI Yf GdfeGPL GdeQcHI(B.s
Keywords: (3GdEbJUGO GdbjGSjs; (3GdYdGbGJ GdEbJUGOjIs